Programmed Cell Death Pathways in the Pathogenesis of Idiopathic Inflammatory Myopathies - Jia Shi (Frontiers Media S.A., 2021)
Idiopathic inflammatory myopathy (IIM) is a heterogeneous group of acquired, autoimmune muscle diseases characterized by muscle inflammation and extramuscular involvements. Present literatures have revealed that dysregulated cell death in combination with impaired elimination of dead cells contribute to the release of autoantigens, damage-associated molecular patterns (DAMPs) and inflammatory cytokines, and result in immune responses and tissue damages in autoimmune diseases, including IIMs. This review summarizes the roles of various forms of programmed cell death pathways in the pathogenesis of IIMs and provides evidence for potential therapeutic targets.